2015
DOI: 10.1111/ajt.13117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Web-Based Training for Department of Motor Vehicle Staff on Donor Designation Rates: Results of a Statewide Randomized Trial

Abstract: On approach to addressing the continual shortage of organ donors is to encourage people to join a state donor registry. Joining the registry saves time and assures family members that organ donation is what their loved one would want. However, fewer than half of adults have taken this step. We tested a brief, webbased training program for department of motor vehicles (DMV) staff that educates them about organ and tissue donation and also models the correct way to interact with customers. The intervention was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 8 publications
0
32
1
Order By: Relevance
“…This was anecdotally successful in increasing rates of organ donor registration, yet through cost‐benefit analyses continued management of the DMV was impossible. Other interventions have successfully documented the increase organ donor registration due to DMV staff training, which may be a promising product to disseminate . Furthermore, there may be limited utilization of the services provided at the DMVs in communities with lower income due to lack of car ownership related to higher concentrated disadvantage.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was anecdotally successful in increasing rates of organ donor registration, yet through cost‐benefit analyses continued management of the DMV was impossible. Other interventions have successfully documented the increase organ donor registration due to DMV staff training, which may be a promising product to disseminate . Furthermore, there may be limited utilization of the services provided at the DMVs in communities with lower income due to lack of car ownership related to higher concentrated disadvantage.…”
Section: Discussioncontrasting
confidence: 99%
“…In West Virginia, staff improved donor registration rates after completing a web‐based training. To expand their impact, these trainings have been offered to be more widely accessible for staff in other DMVs . In addition, mood during DMV experiences was asked about in 3 different models to ultimately elucidate whether frustration at the office was related to organ donor registration.…”
Section: Introductionmentioning
confidence: 99%
“…The sheer number of MVF campaigns is impressive and because of this literature, a formula for what works has emerged. Specifically, MVF campaigns featuring trained MVF clerks, an interpersonal component, video narratives, and point‐of‐decision materials are more likely to increase organ donation registration rates compared to interventions without these elements. That said, these intervention components have demonstrated effectiveness at increasing registrations most typically when statewide registrations are relatively new; however, their effectiveness in MVFs with a mature registry remains understudied (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, one potential downside of relying on volunteers to communicate about organ donation is the cost of managing, organizing, and training those volunteers . Given the influential role interpersonal interactions play inside MVFs, researchers have studied how to train MVF clerks, an improved sustainable alternative to volunteers, to improve their interpersonal interactions with customers regarding organ donation, while at the same time increasing their knowledge about organ donation . Despite the critical nature of MVF clerks in the enrollment process, research has shown that MVF clerks often do not consistently broach the topic of organ donation and unfortunately do not score much better on organ donation knowledge questionnaires than the general public .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation